Food and Identity in Leila S. Chudori's (2015) Home - Cut Syifa Fauzia Abdillah (Universitas Pendidikan Indonesia (UPI), 2022)
In a globalized world, food and foodways can act as vehicle for people to identify their belonging to certain communities or identities. For some people, their longing for certain times, places, or moments, is expressed through food narratives. Basing the analysis on Hall’s (1996) theory of cultural identity, the researcher applies Anita Mannur’s (2010) concept of culinary citizenship and Avtar Brah’s (1996) homing desire as theoretical frameworks, this research aims to reveal the functions and ways food and foodways shape the identities of the main characters of Leila S. Chudori’s (2015) Home. Narrations and dialogues involving food are examined to explore the relationship of an Indonesian political exile in Paris, Dimas Suryo, as well as his daughter, Lintang Utara and food in relation to their identity crises. Based on the analysis, it is found that food functions to claim their identities and as an emotional anchor in their process of constructing and re-constructing their identities as people coming from different generation of immigrants. These results suggest that food and foodways can accentuate the construction of identities of the main characters in the novel as people in diaspora.